Is Polymorphism in the Apoptosis and Inflammatory Pathway Genes Associated With a Primary Response to Anti-TNF Therapy in Crohn’s Disease Patients? - Walczak, Michal; Lykowska-Szuber, Liliana; Plucinska, Marianna; Stawczyk-Eder, Kamila; Zakerska-Banaszak, Oliwia; Eder, Piotr; Krela-Kazmierczak, Iwona; Michalak, Michal; Zywicki, Marek; Karlowski, Wojciech M.; Szalata, Marlena; Dobrowolska, Agnieszka; et al. (Frontiers in Pharmacology, 2020)
Anti-tumor necrosis factor (TNF) therapy is used for the induction and maintenance of remission in Crohn’s disease (CD) patients. However, primary nonresponders to initial treatment constitute 20%–40% of cases. The causes of this phenomenon are still unknown. In this study, we aimed to determine the genetic predictors of the variable reactions of CD patients to anti-TNF therapy. Using long-range PCR libraries and the next-generation sequencing (NGS) method, we performed broad pharmacogenetic studies including a panel of 23 genes (TNFRSF1A, TNFRSF1B, CASP9, FCGR3A, LTA, TNF, FAS, ADAM17, IL17A, IL6, MMP1, MMP3, S100A8, S100A9, S100A12, TLR2, TLR4, TLR9, CD14, IL23R, IL23, IL1R, and IL1B) in a group of 107 diagnosed and clinically characterized CD patients following anti-TNF therapy. In the studied group, we indicated, in total, 598 single nucleotide variants for all analyzed genomic targets. Twelve patients (11.2%) did not respond to the induction therapy, which was associated with alleles in 11 loci located in FCGR3A (rs7539036, rs6672453, rs373184583, and rs12128686), IL1R (rs2041747), TNFRSF1B (rs5746053), IL1B (rs1071676, rs1143639, rs1143637, and rs1143634), and FAS (rs7896789) genes. After multiple comparison corrections, the results were not statistically significant, however for nonresponders the alleles distribution for those loci presented large differences and specified scheme compared to responders and populations. These findings require further investigation in an independent larger cohort before introducing them for a clinical setting, however, we identified an interesting direction. Polymorphism of the FCGR3A, IL1R, TNFRSF1B, IL1B, and FAS genes could be a predictor of the primary response to anti-TNF therapy in CD patients.